Actuality of leadership in the light of modern society’s transformations and its influence to professional training for administrators - Калашнікова, Світлана (Educological discourse, 2013)
The article is devoted to the analysis of society’s development modern trends and their link with education development, in particular, with professional training of administrators in the light of leadership as new paradigm of administration.